2019
DOI: 10.1037/xhp0000610
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory mechanisms influence articulation in the form preparation task.

Abstract: In the form preparation task, participants verbally produce words in small sets, which either overlap on an early phonological fragment or contrast on that fragment. A canonical account of word-form encoding assumes a sequential phonological encoding phase necessarily preceding subsequent retrieval of a discrete phonetic motor plan. This account assumes that acoustic onset and speech onset are equivalent, and that speech onset never precedes complete processing of the stimulus. In two form preparation experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Prior studies have reported similar effects for isolated word production tasks ( Kawamoto et al, 2014 ; Drake and Corley, 2015 ; Tilsen et al, 2016 ; Krause and Kawamoto, 2019 , 2020a ; Tilsen, 2020 ). We believe, however, that this is the first report of such effects in an ecological conversation task.…”
Section: Discussionmentioning
confidence: 56%
“…Prior studies have reported similar effects for isolated word production tasks ( Kawamoto et al, 2014 ; Drake and Corley, 2015 ; Tilsen et al, 2016 ; Krause and Kawamoto, 2019 , 2020a ; Tilsen, 2020 ). We believe, however, that this is the first report of such effects in an ecological conversation task.…”
Section: Discussionmentioning
confidence: 56%
“…However, speakers also produce anticipatory posturing when having partial or less than certain information. Krause and Kawamoto (2019, 2020) gave speakers a series of word‐reading tasks. When the initial consonant was at least 75% predictable, speakers shaped their lips to anticipate it, before the word appeared onscreen.…”
Section: Must Speakers Wait For a Complete Syllable Plan?mentioning
confidence: 99%
“…The benefits offered to phoneticians are obvious and well-established: Kinematics afford a detailed characterization of the motoric mechanisms of speech. However, as we have argued elsewhere (e.g., Kawamoto, Liu, Lee, & Grebe, 2014;Krause & Kawamoto, 2019) psycholinguists examining verbal reaction times also have much to gain from employing articulatory methods. For one thing, articulatory operationalizations of verbal reaction time often tell a very different story than do acoustic ones, in part because different speech-related movements are not obligatorily phase-locked (Kawamoto et al, 2014;Holbrook, Kawamoto, & Liu, 2019).…”
Section: Introductionmentioning
confidence: 83%